PENGEMBANGAN MODEL PERMAINAN DRIBEL BOLABASKET UNTUK PEMBELAJARAN PENDIDIKAN JASMANI KELAS TUJUH SMP NEGERI 15 MALANG - Abi Fajar Fathoni; Oni Bagus Januarto; Febrita Paulina Heynoek (Jurnal Pendidikan Jasmani, 2015)
Abstract: Basketball dribble material is the material that is taught in the phy-sical education teaching for the seventh grade students of SMPN 15 Malang. This research includes research and development. Results of research and development is a model game of basketball dribble. Model game packaged in a pocket book-sized 9 x 13 centimeters. Results of testing a small group of the product obtained eligibility percentage of 86.8%. While large groups of test results obtained eligibility percentage of 88.2%. Key words: game, drible, basketball.  Abstrak: Materi dribel bolabasket merupakan materi yang diajarkan pada pembelajaran pendidikan jasmani untuk siswa kelas tujuh SMP Negeri 15 Malang. Penelitian ini termasuk jenis penelitian dan pengembangan. Hasil dari penelitian dan pengembangan ini adalah model permainan dribel bolabasket. Model permainan dikemas dalam buku saku berukuran 9 x 13 cm. Hasil uji coba kelompok kecil terhadap produkdiperoleh persentase kelayakan sebesar 86,8%. Sedangkan hasil uji coba kelompok besar diperoleh persentase ke-layakan sebesar 88,2%. Kata Kunci: permainan, dribel, bolabasket.